Pembuatan Indeks Koran Singgalang dengan Subjek Cerita Anak di Dinas Perpustakaan dan Kearsipan Kota Padang - Safridar, Widia; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
AbstractIn this paper discussed about the creation of an index of newspaper stories with the subject son Singgalang in the service of the library and Archives of the city of Padang. The purpose of this paper is how stages of making a newspaper index to the subject of children's stories Singgalang in the service of the library and Archives of the city of Padang.Research methods used in the manufacture of the paper is descriptive method in the form of the written word of the document are observed is done by way of observation. The observation is done to obtain data about existing Singgalang newspaper in the service of the library and Archives of the city of Padang.On the basis of the discussion it can be concluded that the stage of the round-the-comic library services library and Archives Office of Padang City elementary school for application of manga maker, as follows: 1) do the observation of Singgalang newspaper; 2) performs the selection against the article; 3) do the newspaper clippings; 4) makes description index newspaper; 5) index; and 6) type index.Keywords: Index, children's stories